Pengaruh Risiko Sistematis dan Likuiditas Perusahaan Terhadap Return Saham pada Perusahaan Sektor Perbankan Yang Terdaftar di LQ45 Bursa Efek Indonesia - Erin Sartika; Destia Aktarina (P3M STIE Mulia Darma Pratama, 2020)
Sampling with quantitative methods, namely a method based on the philosophy of positivism, used to research is generally carried out randomly, obtained 5 companies that meet the criteria. Data analysis using multiple linear regression analysis techniques with the assumption of normality, multicollinearity, heteroskedasticity and autocorrelation. Based on the results of this study it is known that the development of systematic risk, company liquidity and stock returns fluctuated and seen from the output simultaneously obtained fhitung of 20,547 and the ftabel seen in the statistical table with asignificant level of 0,05 with df1n = (number of variables -1) or 3 – 1 = 2, df = (n-k-1) or 30 – 2 – 1 = 27 is 3,35. So the conclusion is fcount > ftabel (20,547 > 3,35) and the significant level is smaller 0,05 (0,000 < 0,05), then HO is rejected and accepts HA. Thus systematic risk and company liquidity simultaneously influence stock returns in banking sector companies listed on the LQ45 Indonesia stock exchange for the period 2012-2017. Based on the results of partial hypothesis testing (t test) of 6,106 and t table which can be seen in the statiistical table which is significant 0,05/2 = 0,025 with degrees of freedom df = n – k – 1 or df 30 – 2 – 1 = 27 results obtained for t table of 2,05183. So the value of tcount > ttable (6,106 > 2,05183) and significantly smaller than 0,05 (0,000 < 0,005), then HO is rejected and accepts HA, thus it can be concluded that systematic risk partially affects stock returns in banking sector companies listed on the indonesia stock exchange LQ45 for the period 2012-2017 and seen from the company’s liquidity output tcount of -1,001 and ttabel which can be seen in the statistical table at the significance of 0,05/2 = 0,025 with degrees of freedom df = n – k – 1 or 30 – 2 – 1 = 27 the results obtained for t table are 2,373 so the value of tcount < ttable (-1,001 < 2,373) and the significance is greater than 0,05 (0,362 > 0,005) then HA is rejected and accepts HO. Thus it can be concluded that partially company liquidity has no effect on stock returns in banking sector companies listed on the LQ45 Indonesia stock exchange for the period 2012-2017.